Analisis Framing Pada Pemberitaan Pelarangan Study Tour Pada Media Kompas.Com Dan Metrotv News.Com - Saputra, Ridwan Agung; Narti , Sri; Dianthi , Martha Herianiazwi (Harmonization : Jurnal Ilmu Sosial, Ilmu Hukum, dan Ilmu Ekonomi, 2024)
This study aims to determine the Syntactic Structure, Script Structure, Thematic Structure, Rhetorical Structure in online media, namely KOMPAS.com and METROTV NEWS.COM. This research reports on the issue and constructs reality in each news script. This study aims to determine the framing of reality constructed by KOMPAS.com and METROTV NEWS.COM in the news text about the Study Tour ban. The method used in this research is descriptive qualitative method, using the framing analysis method of Zhongdang Pan and Gerald M. Kosicki model. The results showed that regarding the Framing Analysis of the Reporting on the Study Tour Ban in the Online Media KOMPAS.com and METROTV NEWS.COM. In this case, it is clear that the two online media both broadcast the same news but with different views. It can be seen that KOMPAS.com and METROTV NEWS.COM online media emphasize more on the prohibition of the Study Tour, namely the Department of Education and Culture, Head (DISDIKBUD) of Central Java Uswatun Hasanah stated that his party would impose strict sanctions on schools that violate these rules. activities that are at great risk and burden students.